Effect of Instant Coffee Consumption Duration on Low Density Lipoprotein (LDL) and Triglyceride Levels in the Community in Tanjung District, North Lombok Regency - Suaryana, I Made Chandra; Wiadnya, Ida Bagus Rai; Dewi, Lale Budi Kusuma; Rohmi, Rohmi (Poltekkes Kemenkes Mataram, 2025)
Long-term coffee consumption is thought to affect health, on blood fat levels such as Low Density Lipoprotein (LDL) cholesterol and Triglycerides. Knowing the effect of length of instant coffee consumption on Low Density Lipoprotein (LDL) and Triglyceride levels in the community in Tanjung District, North Lombok Regency. Analytic observation with a cross-sectional approach. Non-random sampling technique with a sample size of 30 respondents. Data analysis of one way anova test. Average Low Density Lipoprotein (LDL) levels in instant coffee consumers 1 year 175.5 mg/dl, 2 years 227.9 mg/dl, 3 years 296.2 and triglycerides 1 year 107.5 mg/dl, 2 years 165.8 mg/dl, 3 years 159.1 mg/dl. The results of the one-way anova test obtained a sig value of 0.006 ≤ 0.05 and triglycerides 0.007 ≤ 0.05.there is a significant effect of length of instant coffee consumption (1 year, 2 years, and 3 years) on Low Density Lipoprotein (LDL) and Triglyceride levels in the community in Tanjung District, North Lombok Regency. Where the longer the consumption of instant coffee, the higher the levels of Low Density Lipoprotein (LDL) and Triglycerides increased in the first year of instant coffee consumption, but decreased in the third year. This change may be influenced by body adaptation and other factors such as diet, physical activity, and health conditions.